VILLAGE KIAI AND TRANSFORMATIONAL LEADERSHIP: NON-FORMAL EDUCATION MODELS TO IMPROVE THE QUALITY OF COMMUNITY LIFE - Fajriyah, Nurul; Mundiri, Akmal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and study the process of building non-formal education through the transformational leadership of village Kiai. This research was conducted in Sumberrejo village, Paiton subdistrict, Probolinggo district, East Java province. Researchers used a qualitative case study type approach. Data was collected using interview, observation, and documentation techniques and then analyzed through several steps: data collection, data reduction, data presentation, and conclusions. This research shows that the transformational leadership of village Kiai in Karanganyar village is depicted as a spinning wheel to achieve the organization's vision and mission goals. The leadership of the town of Kiai can mobilize the community to develop the knowledge possessed by each individual in the community. In this case, leaders must interact closely with society because leaders must actively motivate to achieve the organization's vision and mission. There are four characteristics of leaders in transformational leadership, namely: (1) Ideaization of Influence/Charisma, (2) Intellectual Stimulus, (3) Intellectual Consideration, and (4) Inspirational Motivation.